Facilitating Young Children's Use of the Web in Preschool. Issue 4 (1st October 2016) - Davidson, Christina; Danby, Susan J.; Given, Lisa M.; Thorpe, Karen J.
ABSTRACT: Current perspectives on young children's use of digital technology suggest that preschool teachers need to provide more effective guidance for children. There is still little research, however, to inform how guidance might be understood and practiced during interactions with digital technology. This article employs an ethnomethodological perspective to examine video-recorded data of a young child and his teacher conducting a Web search to find and view a YouTube video in a preschool classroom. Sequential analysis of interaction, drawing on the techniques of conversation analysis, results in descriptions of the methods used by the child, his teacher, and the other children to accomplish their activity. Discussion considers how interactions produced management of the cohort, promotion of child-centered activity, and development of shared understandings. It is concluded that these constituted use of the Web for the specific setting of preschool.